(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2025)
Scientific Literacy has been consolidated as a central goal in Science Education, and it can be promoted in both formal and non-formal educational settings. This article aims to articulate different perspectives on Scientific Literacy across these spaces in order to propose a broader understanding of the concept. This is a theoretical essay that adopts, as its theoretical framework, the Structuring Axes, Dimensions of Scientific Literacy, and Literacy Premises for formal spaces, alongside the Scientific Literacy Indicators for non-formal environments. Reflections were guided by identifying points of convergence among the perspectives discussed by the authors. The results show that the indicators applied to non-formal settings introduce innovative elements when compared to other frameworks, particularly by emphasizing interactive and institutional aspects of the literacy process. These elements allowed the development of a new perspective, conceptually expanding Scientific Literacy across different educational contexts. We argue that articulating these theoretical perspectives contributes to the consolidation of a more dialogical and contextualized proposal, with potential to guide future actions toward the effective implementation of these perspectives in the context of scientific education.